CHILDBIRTH DEITIES: COMPARATIVE ANALYSIS OF TURK GODDESS UMAY AND CHINESE GODDESS GAOMEI - Д. Сaйкеневa (Journal of Oriental Studies, 2019)
In Turk and Chinese culture childbirth deities have ancient origin. Despite two cultures have different origin: nomad and agriculture civilization, in both praying for childbirth rituals and childbirth deities on semantic level have similarity. During long historical and mythological transformations some rituals lost original meaning. This article reviews similar belief and analyse symbols of childbirth rituals to reveal common and peculiar ideas. Author use survival method to reconstruct lost meaning of some symbols and functions of these deities. Multilingual and semantic analysis reveal fragmentary sayings and relate them to ancient belief, comparing both culture’s common elements reconstruct lost meaning and ideas of these rituals. Key words: praying for childbirth rituals, Umay, Gaomei, symbol.